Solid cancer mortality risk in the Southern Urals populations exposed to radiation cohort: 1950-2019 - L. Yu. Krestinina; S. S. Silkin (Радиационная гигиена)
The objective of the study is to obtain direct risk estimates of solid cancer mortality for members of the Southern Urals Populations Exposed to Radiation Cohort. Materials and methods: the cohort was first created in 2018 and combines all the residents of the Southern Urals exposed to radiation in the territory of the Techa River and East Urals Radioactive Trace. Combining individuals exposed in the two radiation accidents increased the number of cohort members to 62.5 thousand people, the number of solid cancer cases included in the analysis to 4,511 and the number of person-years at risk to 1.956 million with the maximum follow-up period up to 70 years. The analysis was conducted with the use of regression analysis and a simple parametric model for excess relative risk. Maximum likelihood method was used to calculate 95% confidence intervals. Stomach dose was taken as an analogue of the dose to soft tissues accumulated over the entire follow-up period, and calculated using the updated Dosimetry System-2016 in the Urals Research Center for Radiation Medicine. Results: the analysis revealed a statistically significant linear dependence of solid cancer mortality rates on the dose, which confirms and clarifies the conclusions of previous studies. Solid cancer mortality ERR was 0.078/100 mGy. The increase of the statistical power of the analysis due to the increase of the cohort size and extension of the follow-up period enabled to obtain statistically significant ERR values for certain population groups by sex, ethnicity and other parameters. It refines the previously obtained values, reduces uncertainty and allows using the data to refine the radiation safety standards for the population exposed to radiation in various situations.